Analysis of pretreatment factors associated with stability in early class III treatment - Yasuko Inoue; Toru Deguchi; James K. Hartsfield; Wakako Tome; Noriyuki Kitai (SpringerOpen, 2021)
Abstract Background The purpose of this study was to identify pretreatment factors associated with the stability of early class III treatment, since most orthodontists start the treatment with their uncertain hypotheses and/or predictions. Subjects consisted of 75 patients with a class III skeletal relationship (ANB < 2° and overjet < 0 mm) who had been consecutively treated with rapid maxillary expansion and facemask and followed until their second phase treatment. The patients were divided into two groups according to whether they showed relapse in follow-up. The stable group maintained their positive overjet (n = 55), and the unstable group experienced relapse with a zero or negative overjet (n = 20). Two general, three dental, and 13 cephalometric pretreatment factors were investigated to determine which factors were associated with stability. Results Sex, pretreatment age, and anteroposterior functional shift, which were hypothesized as associated factors, were not related to the stability of early class III treatment. Significant differences were detected between the two groups in the horizontal distance between the maxillary and mandibular molars in centric relation. Cephalometric variables, such as the mandibular length (Ar-Me), Wits appraisal, SN to ramus plane angle (SN-Rm), gonial angle, incisor mandibular plane angle (IMPA), and Frankfort plane to mandibular incisor angle (FMIA) showed significant differences between the groups. The horizontal distance was the most influential factor by logistic regression analysis. Conclusions Hypothesis (related to sex, age, functional shift) were rejected. Several cephalometric factors related to the mandible were associated with stability. The horizontal distance between the maxillary and mandibular molars in centric relation was the best predictor of early class III treatment relapse.